Tax Planning Practices in Nepal: A Study on Listed Company in Stock Exchange (The Mega Journal, 2025)
Tax planning is a critical strategy for minimizing tax liabilities through efficient management of business and personal affairs within the confines of the law. This study examines tax planning practices among listed companies in Nepal, focusing on the relationship between strategic, project, and operational tax planning and their impact on tax liability. The research employs a descriptive and causal-comparative design to explore the current tax planning landscape within Nepal’s legal framework and assess the cause-and-effect relationships between various types of tax planning and tax liability. A deductive approach is utilized, with data collected via structured questionnaires from 450 respondents, including accountants and finance managers from Nepal Stock Exchange listed companies. The results, analyzed through SPSS, reveal that strategic tax planning, project tax planning, and operational tax planning significantly impact tax liability, with management efficiency partially mediating these relationships. The study provides valuable insights into the effectiveness of different tax planning strategies and emphasizes the importance of management efficiency in enhancing tax liability management. Future research could explore the broader implications of these findings in other emerging economies.